1
(9-2p^4)²=81-36p^4+4p^8
2
(x^π-y^π)(x^π+y^π)/(x^π+y^π)=x^π-y^π
3
(2-6c-3)(2+6c+3)=(-1-6c)(5+6c)
4
(7m+12p)²
5
1)5 4/45-4 1/15=5 4/45-4 3/45=1 1/45
2)1 1/45*22 1/2=46/45*45/2=23
3)4,25:0,85=5
4)5+0,5=5,5
5)5,56-4,06=1,5
6)1,5:3=0,5
7)5,5:0,5=11
8)23+11=34
Х^3 +4х^2 - 9х-36=0
(х^3+4х^2)-(9х+36)=0
х^2(х+4)-9(х+4)=0
(х+4)(х^2-9)=0
(х+4)(х-3)(х+3)=0
х= -4 х=3 х= -3
Ответ:3;-3;-4
99+1=100. А=9,У=1, Р=0..
20+180=200. М=2, У=0,Б=18.
29+92=121. А=2, У=9, С=1, О=2.
Ответ:
Вроде так. Смотри мы переводим в неправильную дробь и умножаем одну сторону на другую